Leading under pressure : educational leadership in neoliberal times - Chitpin, Stephanie; White, Robert E., active 2022 (Emerald Publishing Limited, 2022)
The best leaders lead by example, not by mandate. However, so much leadership has become conscripted by neoliberal values. Educators and politicians, who are increasingly making policy for educators, have come to believe that standardized test scores are the same as knowledge acquired, as if test scores actually measure knowledge as opposed to information. Simply put, educational policy is no longer being developed for educational purposes but education is increasingly being manipulated as an experiment in social engineering. Educational leaders are caught on the horns of a dilemma - to follow and inscribe policies they do not agree with or to "go rogue" and do what they know is needed. Leading under Pressure is aptly titled, as there is significant pressure being placed on school leaders at any stage in their careers. However, in an otherwise increasingly hostile political, commercial and natural environment, there are some rays of hope. For example, teachers still know what it is that their students need and strive to provide that, despite mandates that try to create consumers of us all. This volume is divided into three sections, the first of which seeks to explore social contexts of educational leadership. The second section explores the experiences of a variety of educational leaders in various contexts, while the third section of this volume looks at some of the consequences, unintended and otherwise, of the neoliberal commodification of education.
Keywords: Educational leadership.; Educational leadership -- Social aspects.; Education and state.; Education -- Leadership.; Organization & management of education.; elektronické knihy; electronic books